Effect of Eight-Weeks Aerobic Training on Serum Levels of Nitric Oxide and Endothelin-1 in Overweight Elderly Men - Reza Mohammadi; Mehrdad Fathei; Keyvan Hejazi (University of Social Welfare & Rehabilitation Sciences, 2018)
Objectives Different physical activities can play an important role in improving health and cardiovascular fitness. The aim of this study was to compare the effect of high-intensity interval aerobic training on certain cardiovascular risk factors in overweight elderly men. Methods & Materials In this semi-experimental study, 24 overweight elderly men were selected by convenience sampling. They were then randomly assigned into two groups based on their body mass index (BMI). The age range in the experimental group was 73.50±3.34 years (n=12) and that in control group was 71.33±3.44 years (n=12). The experimental group underwent high-intensity interval aerobic training that included 3 sessions (each of 45-60 minutes) a week for eight weeks. The control group was given no intervention.  Blood samples of all the subjects were measured at baseline and at the end of the study. All tests were two-tailed, and P<0.05 was considered significant. Data analysis was performed using SPSS software (version 16.0, SPSS). For comparison of means within and between the groups, paired and independent t-tests were used, respectively.   Results The weight, BMI, and body fat percentage were found to have significantly decreased in overweight men after high-intensity interval aerobic training (P<0.05). Moreover, the levels of serum endothelin-1 reduced significantly after eight weeks of aerobic training. However, the levels of nitric oxide increased significantly at the end of the training period.  Conclusion This result suggests that eight weeks of high-intensity interval aerobic training led to decreased endothelin-1 serum and increased nitric oxide levels. This is effective in improving cardiovascular health and reducing the risk of atherosclerosis. Therefore, it is suggested that high-intensity interval aerobic training be used to prevent the adverse effects of an increased incidence of atherosclerosis.